A family study of congenital X linked sideroblastic anaemia. Issue 1 (January 1990) - Holmes, J; May, A; Geddes, D; Jacobs, A
Abstract : We report on the cytogenetic findings in a family study of pyridoxine responsive, X linked sideroblastic anaemia. An increase in the number of X chromosomes was observed in a small proportion of metaphases prepared from five female members, but these findings did not strictly correlate with the carrier status of the condition. No consistent cytogenetic abnormality could be identified or associated with this rare familial condition. The diagnosis and counselling of carriers of this condition is discussed.